Short-term priming, concurrent processing, and saccade curvature during a target selection task in the monkey - McPeek, Robert M.; Keller, Edward L. (Vision research (Oxford), 2001)
In human subjects, two mechanisms for improving the efficiency of saccades in visual search have recently been described: color priming and concurrent processing of two saccades. Since the monkey provides an important model for understanding the neural underpinnings of target selection in visual search, we sought to explore the degree to which the saccadic system of monkeys uses these same mechanisms. Therefore, we recorded the eye movements of rhesus monkeys performing a simple color-oddity pop-out search task, similar to that used previously with human subjects. The monkeys were rewarded for making a saccade to the odd-colored target, which was presented with an array of three distractors. The target and distractors were randomly chosen to be red or green in each trial. Similar to what was previously observed for humans, we found that monkeys show the influence of a cumulative, short-term priming mechanism which facilitates saccades when the color of the search target happens to repeat from trial to trial. Furthermore, we found that like humans, when monkeys make an erroneous initial saccade to a distractor, they are capable of executing a second saccade to the target after a very brief inter-saccadic interval, suggesting that the two saccades have been programmed concurrently (i.e. in parallel). These results demonstrate a close similarity between human and monkey performance. We also made a new observation: we found that when monkeys make such two-saccade responses, the trajectory of the initial saccade tends to curve toward the goal of the subsequent saccade. This provides evidence that the two saccade goals are simultaneously represented on a common motor map, supporting the idea that the movements are processed concurrently. It also indicates that concurrent processing is not limited to brain areas involved in higher-level planning; rather, such parallel programming apparently occurs at a low enough level in the saccadic system that it can affect saccade trajectory.